Biomimetic Scaffolds Modulate the Posttraumatic Inflammatory Response in Articular Cartilage Contributing to Enhanced Neoformation of Cartilaginous Tissue In Vivo (Adv. Healthcare Mater. 1/2022). Issue 1 (4th January 2022) - Bauza‐Mayol, Guillermo; Quintela, Marcos; Brozovich, Ava; Hopson, Michael; Shaikh, Shazad; Cabrera, Fernando; Shi, Aaron; Niclot, Federica Banche; Paradiso, Francesca; Combellack, Emman; Jovic, Tom; Rees, Paul; et al.
Abstract : Cartilage Repair In article number 2101127 by Lewis W. Francis, Francesca Taraballi, and co‐workers, a biomimetic immune tuning scaffold is implanted in a full‐thickness chondral defect in rabbits. The early inflammatory infiltrates changed in the treated animals resulting in a better cartilage homeostasis at longer timepoints. This work represents the first approach of tuning the inflammatory reaction with a bulk material to achieve a better regeneration in cartilage.